Alterations in scale: Patterns of change in main street networks across time and space. (December 2014) - Porta, Sergio; Romice, Ombretta; Maxwell, J Alexander; Russell, Peter; Baird, Darren
This paper presents a morphological study of 100 main street networks from urban areas around the world. An expansion in the scale of main street networks was revealed using a unique heuristic visual method for identifying and measuring the lengths of main street segments from each of the study areas. Case studies were selected and grouped according to corresponding urban design paradigms, ranging from antiquity to present day. This research shows that the average lengths of main street segments from networks of historic (i.e. ancient, medieval, renaissance, baroque and industrial) and informal case studies are much smaller relative to those from networks of more contemporary case studies (i.e. Garden City, Radiant City and New Urbanism). This study provides empirical evidence in support of prior, observational claims suggesting a consistent pattern in the smaller scale of main street networks from traditional urban areas, termed the '400-metre rule'. Additionally, it makes the case for further empirical research into similarly recursive spatial patterns within other elements of urban form (i.e. plots, blocks, etc.) that, if discovered, could aid in future urban design efforts to help provide the framework for more 'human-scale' urban environments.